2019
DOI: 10.3389/fimmu.2019.00544
|View full text |Cite|
|
Sign up to set email alerts
|

Inside-Out Control of Fc-Receptors

Abstract: Receptors recognizing the Fc-part of immunoglobulins (FcR) are important in the engagement of phagocytes with opsonized micro-organisms, but they also play a major role in the pathogenesis of chronic inflammatory diseases. Different FcRs are specifically recognizing and binding the different classes of immunoglobulins, transmitting different signals into the cell. The function of IgG (FcγR's) and IgA (FcαR) recognizing receptors is controlled by cellular signals evoked by activation of heterologous receptors i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 102 publications
0
45
0
Order By: Relevance
“…It is feasible that upon activation with immune complexes, macrophage FcRs may pair with different membrane proteins. Cell surface receptor interactions and crosstalk between signaling pathways might represent important regulatory mechanisms (Rittirsch et al, 2009;van Egmond et al, 2015;Koenderman, 2019), influencing parasite entry into the cell.…”
Section: Discussionmentioning
confidence: 99%
“…It is feasible that upon activation with immune complexes, macrophage FcRs may pair with different membrane proteins. Cell surface receptor interactions and crosstalk between signaling pathways might represent important regulatory mechanisms (Rittirsch et al, 2009;van Egmond et al, 2015;Koenderman, 2019), influencing parasite entry into the cell.…”
Section: Discussionmentioning
confidence: 99%
“…Can be divided into inhibitory (FcγRIIB) and activating receptors (FcγRI, FcγRIIA, FcγRIIC, FcγRIIIA, and FcγRIIIB). Through binding of IgG via the Fc portion, FcγRs are essential for regulating responses to infections and controlling inflammation (8, 9).…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps, but it could be noticed that some mutations suppressing the inhibitor receptor have been associated with increasing macrophage phagocytosis of Plasmodium (42). Moreover, the mechanism called "insideout control" and well reviewed by Koenderman et al (43) could may be explained how FcgRIIB apparently in low number succeed to inhibit FcgRIIA's activity. Indeed, by modulating the affinity, i.e., the strength of the receptor for its ligand, modulating the valency or the engagement of multiple receptors, modulating the interaction with the signal chains, the other receptors, or their localization in the various membranes, it is possible to regulate the function of the receptors.…”
Section: The Structure and Function Of Fc Gamma Receptorsmentioning
confidence: 99%
“…The expression of the FcgRIIIA receptor has been indicated to be influenced by the glycosylation. The review by Koenderman et al (43) mentioned that an ectopically expressing tail-less version of FcgRIIB could weaken the signal response. Again, some studies have shown that a mutation in FCGR2C genes to a stop codon leads to the expression of FcgRIIB in NK cells with consequences of inhibiting its function (34,48).…”
Section: The Structure and Function Of Fc Gamma Receptorsmentioning
confidence: 99%